2013
DOI: 10.1371/journal.pone.0068144
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Bloodstream Infections in Brazilian Pediatric Patients: Microbiology, Epidemiology, and Clinical Features

Abstract: BackgroundNosocomial bloodstream infections (nBSIs) are an important cause of morbidity and mortality and are the most frequent type of nosocomial infection in pediatric patients.MethodsWe identified the predominant pathogens and antimicrobial susceptibilities of nosocomial bloodstream isolates in pediatric patients (≤16 years of age) in the Brazilian Prospective Surveillance for nBSIs at 16 hospitals from 12 June 2007 to 31 March 2010 (Br SCOPE project).ResultsIn our study a total of 2,563 cases of nBSI were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
33
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 19 publications
13
33
4
6
Order By: Relevance
“…The presence of TEM, SHV and CTX-M genes alone in the study of Alibi et al in Tunisia was high compared to our results with 3.39% (4/118), 4.23% (5/118) and 11% (13/118) respectively [54]. In Mozambique, on 19 [57]. It is observed that the expression of bla CTX-M is currently more prevalent and as we report for the first time in Togo, more frequent in a triple combination with bla TEM and bla SHV .…”
Section: Discussioncontrasting
confidence: 68%
“…The presence of TEM, SHV and CTX-M genes alone in the study of Alibi et al in Tunisia was high compared to our results with 3.39% (4/118), 4.23% (5/118) and 11% (13/118) respectively [54]. In Mozambique, on 19 [57]. It is observed that the expression of bla CTX-M is currently more prevalent and as we report for the first time in Togo, more frequent in a triple combination with bla TEM and bla SHV .…”
Section: Discussioncontrasting
confidence: 68%
“…In recent years, however, they have been related to important nosocomial infections, mainly in weakened and elderly patients and low-weight infants. (15,16) In addition, some species produce a slime layer of polysaccharides that increases the bacterial adhesion to the different surfaces and is related to the formation of biofilms. (17,18) The susceptibility profile of the Staphylococcus revealed that, of all isolated strains, 61.5% were oxacillin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The IV route was chosen because it is a common method of administration for both antimicrobial and anticancer drugs. Pseudomonas aeruginosa is one of the most common nosocomial causes of Gram-negative infections and bacteremia, 33 and thus it is especially relevant to patients with septicemia or undergoing IV therapies. To prepare the bacterial suspension for IV injection, an aliquot of a stock of P. aeruginosa was added to tubes containing tryptic soy broth.…”
Section: Bacterial Preparation and Administrationmentioning
confidence: 99%